Creating Customer Satisfaction to Customer Loyalty: The Role of Service Quality in Every 'Moment of Truth' - Febrisi Dwita; Leony Agustine (Business and Entrepreneurial Review, 2023)
This study aims to examine a model that evaluates the relationship between the moment of truth, service quality, and customer satisfaction on loyalty. This research was conducted at courier logistics in Bekasi City, West Java Province, Indonesia. This research was conducted from June 2022 to February 2023. The population in this study are customers who have used courier logistic services for an unknown number. This study used a simple random sampling technique and for the sample, 138 respondents participated, but only 98 completed questionnaires were deemed useable. The data analysis uses the SEM-PLS technique. The results of this study are that there is a positive relationship between the moment of truth and customer satisfaction, where when the customer is using the delivery service for the first time and has a good impression of the company's services, it can affect perceptions about the ability and use of these services from time to time. The experience of using the service can change the priorities that underlie each customer's main reason. There is a positive influence between Service Quality on customer satisfaction, where when the delivery service company provides maximum service quality, customers will feel and will reuse their services which can even make these customers more loyal to the company. There is a positive influence between customer satisfaction on loyalty, the moment of truth has a positive influence on customer loyalty, and service quality has a positive influence on customer loyalty.